Pengaruh Kepercayaan, Kemudahan Platform, dan Akuntabilitas Perusahaan terhadap Minat Masyarakat Menggunakan Fintech Crowdfunding Kitabisa di Karawang - Siti Nuraeni Meida Yanti; Sihabudin Sihabudin; Robby Fauji (Jurnal Manajemen dan Ekonomi Kreatif, 2026)
This study discusses the influence of trust, platform ease of use, and business accountability on public interest in the Kitabisa.com fintech crowdfunding platform in Karawang. Using a quantitative approach with a survey method, this study involved 112 participants, analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with the aid of SmartPLS 4.0. The results indicate that all three variables trust, ease of use, and accountability have a significant impact on user interest. Among these variables, accountability proved to be the most dominant factor in influencing user interest. The model used in this study explained 53.0% of the variation in user interest, reflected in the R-square value of 0.530. These findings emphasize that transparency, trust, and ease of service are key components in encouraging public participation and use of the fintech crowdfunding platform. Therefore, to increase user interest, it is essential for platform providers to focus on improving accountability and ease of access, as well as building trust with users through better transparency in platform management and oversight.